The effects of a 160 km run on selected anthropometric, physiological and psychological parameters - Oltmann, Carmen (Rhodes University, Faculty of Science, Department of Human Movement Studies, 1992)
Twenty-one male subjects volunteered to participate in this study of the effects of an ultramarathon run under competitive conditions. Selected anthropometric measurements were made before and after the race. Blood samples were taken before, and within 10 min. of completing the race. Haematocrit and cortisol concentrations were analysed from each sample. Three ratings of perceived exertion (RPE) - local, central and overall, were obtained at two-hourly intervals throughout the race. The shortened form of the Eysenck Personality Inventory (EPI) was administered before the race. The Profile of Mood States (POMS) test was completed both before and immediately after the race. The average running intensity was estimated to be about 32% VOâ‚‚max which would not have caused major lactate accumulation. Repetitive compressive forces as a result of heel-strike resulted in intervertebral disc fluid loss. This resulted in a significant (p<0.05) decrease in stature after the race. Mobilization of glycogen, trig1ycerides and protein for metabolism as well as fluid loss via sweat resulted in significantly decreased body mass after the race. Plasma volume and serum cortisol concentrations were significantly increased after the race compared to pre-race baseline levels. Local RPE responses were dominant throughout the entire race, followed by overall RPE. Running 160 km had an effect on mood state. "Depression", "fatigue" and "confusion" (profile of Mood states) were all significantly increased compared to pre-race scores. Sleep deprivation as a result of running through the night was probably an important contributing factor. The anthropometric profile of the ultramarathon runners in this sample was more like that of the general population than elite marathon runners from the literature. The ultramarathon runners were more extroverted than elite marathon runners, but exhibited a similar Profile of Mood state before the race. The stressor - running 160 km - resulted in a 'strain response'. This was evident in the decreased stature and mass, and increased serum cortisol, "depression", "confusion" and above all "fatigue".
Keywords: Marathon running -- Psychological effects; Marathon running -- Physiological effects